Competitive balance in Veikkausliiga and Liiga - Töllikkö, Roope (2020)
Since the nominal paper by Simon Rottenberg in 1956, in which he discussed the notion of competitive balance for the first time, the theory has been a backbone in team sport economics. However, recent empirical evidence shows a clear trend of decrease in the levels of competitive balance across different leagues and sports around the world. A clear gap in the evidence exists in the Finnish sporting context and therefore this thesis aims to determine the current levels of competitive balance in Veikkausliiga and Liiga and how these levels have evolved throughout the last 30 years (1990-2019). The theoretical framework of this thesis can be traced to Simon Rottenberg’s theory of competitive balance and uncertainty of outcome, which is widely considered as the kick-start for team sport economics. The theory states that in order for a sport league to thrive, to attract spectators and thus be more profitable, the teams must be of approximately similar strength. Dominance, or in other words, a monopoly position of one or a few teams would harm the league, the main product itself. In order to measure the levels of competitive balance in the two leagues, a series of widely established measurement methods were used. The tools included the Herfindahl-Index, Gini Coefficient, standard deviation and historical winning percentages. The results show that, on average, competitive balance has improved in Liiga over the research period, whilst it has remained relatively stagnant in Veikkausliiga.